IMPLEMENTASI KARTU PANTAU KONSUMSI PEMBERIAN MAKANAN TAMBAHAN PROGRAM DAN TABLET TAMBAH DARAH DALAM PENCEGAHAN IBU HAMIL KURANG ENERGI KRONIK DAN ANEMIA - Simbolon, Demsa; Desri Suryani; Lia Lorena; Marbun, Revi Herlina; Ningsih, Lisma; Hasmanita, Maharani Mirabella; Febrina, Amelia (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The current government program is focused on accelerating the reduction in stunting prevalence to 14% by 2024. Various efforts are made by involving all sectors, one of which is higher education through Community Service activities. The method uses a community empowerment approach starting from socialization activities, cadre training, and mentoring pregnant women with Chronic Energy Deficiency (SEZ) and Anemia. The activities aim to empower health cadres in the Implementation of Monitor Cards for SFP and Iron Tablet Consumption. Partners of activities are Puskesmas Leaders and Nutrition Officers (3 people), Regional Apparatus (2 people), Health Cadres (10 people), and pregnant women at risk of SEZ and Anemia (17 people). The implementation of activities from May to November 2023. Monitor Cards for Additional Food Consumption, iron tablets, and educational media booklets are the science and technology applied. Success indicators will be analyzed by comparing pre-test and post-test results. The results of these activities are in the form of the formation of cadres assisting pregnant women, increasing cadre knowledge (from an average score of 88.5 to 98.5), positive attitudes of cadres (from an average score of 2.8 to 3.33), and increasing the ability of cadres to assist in training. Increased knowledge of pregnant women (from an average score of 68.33 to 82.86), positive attitudes of pregnant women (from an average score of 2.83 to 3.14), and actions of pregnant women (from an average score of 60 to 74.76). --- Program pemerintah saat ini difokuskan untuk percepatan penurunan prevalensi stunting 14% pada tahun 2024. Berbagai upaya dilakukan dengan melibatkan semua sektor, salah satunya perguruan tinggi melalui kegiatan Pengabdian kepada Masyarakat (PKM). Metode PMK menggunakan pendekatan pemberdayaan masyarakat yang dimulai dari kegiatan sosialisasi kegiatan, pelatihan kader, dan pendampingan ibu hamil berisko KEK dan Anemia. Tujuan PKM untuk memberdayakan kader kesehatan dalam Implementasi Kartu Pantau Konsumsi PMT Program dan TTD. MITRA kegiatan adalah Pimpinan Puskesmas dan Petugas Gizi Puskesmas (3 orang), Perangkat Daerah (2 orang), Kader Kesehatan (10 orang), dan Ibu hamil berisiko KEK dan Anemia (17 orang). Pelaksanaan kegiatan dari bulan Mei-November 2023. Ipteks yang diterapkan berupa Kartu Pantau Konsumsi Makanan Tambahan dan tablet tambah darah, serta Booklet media edukasi. Indikator keberhasilan akan dianalisis dengan membandingkan hasil pre-test dan post-test. Hasil Kegiatan PKM berupa terbentuknya kader pendemping ibu hamil, peningkatan pengetahuan kader (dari rata-rata skor 88,5 menjadi 98,5), sikap positif kader (dari rata-rata skor 2,8 menjadi 3,33) dan peningkatan kemampuan kader melakukan pendampingan setelah pelatihan. Peningkatan pengetahuan ibu hamil (dari rata-rata skor 68,33 menjadi 82,86), sikap positif ibu hamil (dari rata-rata skor 2,83 menjadi 3,14), dan tindakan ibu hamil (dari rata-rata skor 60 menjadi 74,76).